GEBELİKTE KARACİĞER HASTALIKLARI - ÖZDEMİR, Sebati and Akın, Perihan (Cerrahpaşa Medical Journal, 2014)
Background.- Liver disease is rare in pregnancy, occurring in less than 0.1% of pregnancies. Liver disease in pregnancy generally falls into two categories. The first are liver diseases unique to pregnancy consisting of hyperemesis gravidarum, intrahepatic cholestasis of pregnancy, acute fatty liver of pregnancy, toxemia of pregnancy and HELLP syndrome. The second are liver diseases that occur during pregnancy such as acute viral hepatitis or pregnancy in patients with preexisting liver disease such as chronic hepatitis or liver cirrhosis. When a pregnant woman presents with liver disease, whether the condition is unique to pregnancy must be investigated first. This article briefly examines liver diseases in pregnancy.